Transformative innovation policy: some theoretical and international practical issues - Bui Ngoc Thu Ha; Dang Thu Giang (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
Faced with a rapidly changing and volatile global context, many countries have realized the need for a new approach to Science, Technology, and Innovation (STI) to address the major challenges of sustainable development, including economic, social, and environmental aspects. Among these, the Transformative Innovation Policy (TIP) framework has emerged as an appropriate approach to promote innovation and enhance coordination among stakeholders to provide comprehensive and radical solutions to these issues. This article explores some theoretical and practical issues related to the development of TIP in different countries around the world to address the major challenges of today. Code: 23020802